Photodegradation of tetracycline and sulfathiazole individually and in mixtures. (June 2018) - Yun, Seong Ho; Jho, Eun Hea; Jeong, Seulki; Choi, Soobin; Kal, Youngjoo; Cha, Sangwon
Abstract: Antibiotics in environment can be of concern as they can enter the food chain posing risks to ecosystems and human health. Photodegradation has been considered as a promising way of naturally degrading antibiotics in environment. Antibiotics are usually present in mixtures in environment; however, previous studies focused on individual compounds. Therefore, this study investigated the effect of UV irradiation on the degradation of tetracycline (TC) and sulfathiazole (STH) in individual solutions and mixtures. Under dark conditions, the initial masses of TC and STH were reduced by about 35% and 26%, respectively, over a 35 d-reaction period. With UV irradiation TC and STH were completely removed within 14 d and 35 d, respectively, regardless of the initial concentrations. Both the TC and STH removals were faster (i.e., 2–4 times) when they were in mixtures. This may be partly attributed to the byproducts such as sulfate that can promote indirect photolysis and partly to the enhanced hydrolysis due to changes in the solution pH. Overall, this study suggests that when photodegradation is used to remove antibiotics in water, the removal kinetics of antibiotics individually and in mixtures can be considered to develop more efficient treatment technologies. Highlights: UV photolysis reduced tetracycline (TC) and sulfathiazole (STH) in water. Removal of TC and STH was faster in mixtures than in individual solutions. Faster removal may be due to byproducts like sulfate and decreases in pH. Removal rates, individually and in mixture, should be considered for better treatment.